Efektivitas Pelaksanaan Tugas Pemerintah Desa Dalam Pembangunan Di Kecamatan Modayag Barat Kabupaten Bolaang Mongondow Timur. - Rompas, Sonny (JURNAL ADMINISTRASI BISNIS, 2014)
Implementation tasks for the village government is still faced with several problems and obstacles such as low quality of human resources the village government officials, low morale and discipline of government officials working village that caused partly by low welfare and incentives received, inadequate infrastucture facilities of work, and etc. all of which ultimately impact the performance of duties is not maximal effectiveness of village government. The purpose of this study is to examine the effectiveness of implementation of tasks in the construction of village government in the district of West Modayag Bolaang Mongondow East. This study uses qualitative methods. Data sources (informants) study with purposive sampling technique was taken from a variety of elements related to governance and development in all villages in the district of West Modayag, is elements of the village goverment, the element of BPD, and elements of social institutions. The number of informants all 15 people (taken 3 people per village). Data / Informan collected through interview techniques and observation techniques are equipped with a main instrument is the researches themselves. The collected data were analyzed with a qualitative analysis technique that is interactive analysis model, then the results of the analysis presented in narrative form. The results showed : (1) The duty of the government in the development of the village seen from the task of coordinating and facilitating the planning and implementation of participatory rural development in all villages of West Modayag district was not maximal but effective enough. (2) The duty of the government in the development of the village seen from the task of mobilizing and developing community participation in rural development has not yet been sufficiently effective maximum. Based on the results of these studies concluded that the effectiveness of implementation of tasks in the village government development in the villages in the district of West Modayag not maximized but it can already be said to be quite effective. Keywords : Implementation tasks, the village government